The sports commitment in football players and its relationship with the coach professional performance - Notario-Alonso, R.; Prieto-Ayuso, A.; García-Notario, A.; Contreras-Jordán, O. R. (Journal of Human Sport & Exercise, 2023)
The objective of the article was to relate the sports commitment of the football players together with the performance of the coach to test the relationship that both have with the sporting success of the football players. The PRISMA methodology was used. The Web of Science, Scopus, Academic Search Ultimate, Eric, Medline and Sport Discuss databases were used, with no time limit. The PICO strategy was used to screen articles. Finally, a total of 8 articles were included in the review. The importance between the commitment and the interpersonal style of the coach was demonstrated, which includes aspects in relation to his way of working globally, which we call performance. An increase in the level of commitment was also observed as the performance of the coach improved, especially the motivational climate that this produces in the players. For this reason, it is necessary to take care of these aspects in coaches when they work with potential sports talent.